Characteristics of Two-Year College Students on the Autism Spectrum and Their Support Services Experiences - Roux, Anne M. (Autism Res Treat, 2015)
Approximately 80% of college-going youth with autism in the US attend a 2-year college at some point. These community-based, universally accessible institutions offer both academic and vocational courses and have experience in teaching diverse learners. This study used nationally representative survey data from the National Longitudinal Transition Study-2 to describe the characteristics and services experiences of adults with autism who attended postsecondary education after high school, focusing on those who attended a 2-year college. Over 60% of those who attended 2-year colleges had little to no trouble conversing or performing functional skills like counting change during high school, and extracurricular participation was common (93.8%). Most 2-year college attenders (85.7%) were able to navigate to places outside the home versus 43.9% of those with no postsecondary education. Over half took vocational courses at 2-year colleges, while one-quarter pursued academic study. Less than half (48.6%) of those who disclosed their disability to the school reported receiving services, accommodations, or other help. Most (87.3%) felt they received enough help, but fewer (68.0%) felt the services they received were useful. Future research should delineate specific needs of students with autism in 2-year college settings and identify what supports are needed to improve persistence and completion rates.